Tiempo promedio de pacientes en los consultorios externos de pediatría, medicina general y reumatología del Hospital Walter Cruz Vilca- Alto Moche, setiembre-octubre 2011 - Medina Pérez, Teresa Eurosina (2011)
This research was used to determine the average time delay of the patient in Pediatrics, General Medicine and Rheumatology clinics, of the Vilca Walter Cruz Hospital - Alto Moche. This was observed for 20 days the behavior of arrivals and service times of patients attending the clinics of pediatrics, general medicine and rheumatology at the same hospital. The methodology used was the waiting line Model with a single server, which is applied independently to each doctor's office, it was found that patient arrivals to each of the clinics follow a Poisson distribution, so it is verified that the service times follow an exponential distribution. In pediatric room, it was determined that the average time in queue was about 11 minutes and the time within the system, about 20 minutes, the average number of patients in the waiting line was less than 1 and the system approximately 1.9 patients. In general practice, it was determined that the average time in the waiting line was approximately 7 minutes and the time within the system of about 18 minutes, the average number of patients in the waiting line was 0.29 and 0.70 in the system aboutpatients. In the rheumatology clinic, it was determined that the average time in the waiting line was approximately 7.5 minutes and the time within the system about 18 minutes, the average number of patients in the waiting line was 0.30 and the system approximately 0.73 patients